2017
DOI: 10.1016/j.autneu.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

CNS sites activated by renal pelvic epithelial sodium channels (ENaCs) in response to hypertonic saline in awake rats

Abstract: In some patients, renal nerve denervation has been reported to be an effective treatment for essential hypertension. Considerable evidence suggests that afferent renal nerves (ARN) and sodium balance play important roles in the development and maintenance of high blood pressure. ARN are sensitive to sodium concentrations in the renal pelvis. To better understand the role of ARN, we infused isotonic or hypertonic NaCl (308 or 500 mOsm) into the left renal pelvis of conscious rats for two hours while recording a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Activation of renal sensory afferent fibers by a high sodium diet decreases efferent sympathetic signals, which increases urinary sodium excretion to maintain sodium homeostasis 19 . Experiments in rats demonstrated that normal saline had little effect on afferent nerve activity, while hypertonic NaCl elicited an increase in renal afferent nerve activity 29 . On the other hand, experimental evidence shows that the afferent signaling resulting from renal injury increases efferent renal sympathetic activity leading to hypertension 30 .…”
Section: Renal Sympathetic Innervation: Physiological Role Of Efferenmentioning
confidence: 98%
“…Activation of renal sensory afferent fibers by a high sodium diet decreases efferent sympathetic signals, which increases urinary sodium excretion to maintain sodium homeostasis 19 . Experiments in rats demonstrated that normal saline had little effect on afferent nerve activity, while hypertonic NaCl elicited an increase in renal afferent nerve activity 29 . On the other hand, experimental evidence shows that the afferent signaling resulting from renal injury increases efferent renal sympathetic activity leading to hypertension 30 .…”
Section: Renal Sympathetic Innervation: Physiological Role Of Efferenmentioning
confidence: 98%
“…Adequacy of the anesthesia was confirmed by the lack of the response to paw pinches during the surgical procedure. The direct recording of ARNA with intrapelvic injections was performed as described previously [24,26,34,35]. Briefly, the left kidney was exposed through a retroperitoneal flank incision.…”
Section: Intrapelvic Injection Of Glp-1 With Direct Recording Of Affementioning
confidence: 99%
“…In contrast, R2 chemoreceptors are active in the resting state and are slowly-adapting insofar as their firing continues 15–20 min after death. They are activated by renal ischemia and by backflow of hypertonic or hyperosmotic urine (Recordati et al, 1980; Goodwill et al, 2017). Studies pointed toward a role for chemoreceptors in initiating an excitatory reno-renal reflex, which contributes to sympathoexcitation and blood pressure elevation (Calaresu et al, 1976; Recordati et al, 1978; Goodwill et al, 2017).…”
Section: Renal Sensory Afferent Nervesmentioning
confidence: 99%
“…They are activated by renal ischemia and by backflow of hypertonic or hyperosmotic urine (Recordati et al, 1980; Goodwill et al, 2017). Studies pointed toward a role for chemoreceptors in initiating an excitatory reno-renal reflex, which contributes to sympathoexcitation and blood pressure elevation (Calaresu et al, 1976; Recordati et al, 1978; Goodwill et al, 2017). To distinguish the role of mechanoreceptors from that of chemoreceptors, an increase in renal pelvic pressure over a physiological range (2.5–10 mmHg) was utilized to activate the mechanoreceptors while a solution of 450 mM NaCl was used to stimulate the chemoreceptors (Kopp et al, 1998b; Wainford and Frame, 2017).…”
Section: Renal Sensory Afferent Nervesmentioning
confidence: 99%